Traffic Information System Kuala Lumpur / Tay Tick Seng - Tay , Tick Seng (2003)
Traffic Information System (TIS) Kuala Lumpur is a web based system that providing traffic information to the road user. Besides, road user can retrieve road info depend on their need from the web site in order to avoid traffic congestion in Kuala Lumpur City. The main purpose of this TIS is to let road user know the traffic condition in any time from the internet before begin their trip to Kuala Lumpur city, rather than go towards Kuala Lumpur City without knowing traffic info in particular area. TIS will help user avoid traffic jam in certain areas and save their precious time. When they know traffic jam I particular area, they can find alternative way to their destination. A registered user can conduct more functionalittes like preset their info in the website after login. Literature review had been done in various topics about Traffic Information System. Existing System Studies were done to survey the requirement and some related info from the systems. The ways to obtain info are informal interview, reading material, researching through mtemet and etc. The overall system development strategy of TIS is Unified Software Development Process (USDP). Diagram like Use Case, Collaboration, Class and etc. are use to model the TIS. The web server of TIS is Internet Information Server (liS) and database server is SQL server. Active Server Pages .NET (ASP.NET) is the main programming language technology to develop the system based on the system requirement.